Food properties handbook (CRC Press, 2009)
Dramatically restructured, more than double in size, the second edition of the Food Properties Handbook has been expanded from seven to 24 chapters. In the more than ten years since the publication of the internationally acclaimed and bestselling first edition, many changes have taken place in the approaches used to solve problems in food preservation, processing, storage, marketing, consumption, and even after consumption. Incorporating changes too numerous to list, this updated edition provides new measurement techniques, basic data compiled for diversified food groups, worked-out examples, and detailed graphs and illustrations.